2020
DOI: 10.1039/c9ob02639h
|View full text |Cite
|
Sign up to set email alerts
|

Formal enantioselective synthesis of nhatrangin A

Abstract: A new and straightforward synthesis of the C1–C7 core fragment of nhatrangin A was achieved in 14 steps from achiral 3-hydroxybenzaldehyde, without the need of chiral reagents or enzymatic resolution to introduce the chiral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“… 94 In continuation of this work, Feuillastre et al reported the enantioselective synthesis of the C1–C7 fragment 206 of nhatrangin A 207 in 2020 ( Scheme 23 ). 95 It was a 14-step sequenced methodology, starting from the easily available achiral 3-hydroxybenzaldehyde, and the overall yield was 13%. The main steps in their scheme were Sharpless asymmetric epoxidation and Gilman reagent-induced regioselective epoxide ring opening reaction.…”
Section: Review Of Literaturementioning
confidence: 99%
“… 94 In continuation of this work, Feuillastre et al reported the enantioselective synthesis of the C1–C7 fragment 206 of nhatrangin A 207 in 2020 ( Scheme 23 ). 95 It was a 14-step sequenced methodology, starting from the easily available achiral 3-hydroxybenzaldehyde, and the overall yield was 13%. The main steps in their scheme were Sharpless asymmetric epoxidation and Gilman reagent-induced regioselective epoxide ring opening reaction.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Nhatrangin A was also proposed as a biosynthetic intermediate of ATX/OTX due to the structure similarity. To date, three total syntheses and a formal total synthesis of 2 have been reported by Kamal, Yadav, Dias, and Piva, respectively. The NMR spectra reported by Kamal and Yadav were in good agreement with those of the natural product, but did not match those of nhatrangin A as synthesized by Dias, raising questions as to the accuracy of the proposed relative configuration of 2 .…”
mentioning
confidence: 99%